2010
DOI: 10.1016/j.ijimpeng.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of blast wave effects on a developed site

Abstract: The guidelines for protecting against and mitigating explosion hazards require knowledge and either the experimental or theoretical evaluation of blast wave parameters. To this end, this article proposes a numerical method for simulating blast wave propagation in complex geometries. This method permits an on-the-ground TNT-like explosion and the subsequent blast wave to be simulated, with the possibility of modifying the ground topology by adding a number of obstacles. The numerical model is explored from both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The data presented in the current paper may be used as the validation input for the numerical, analytical, or experimental studies. For instance, the data would be useful to validate the numerical model discussed in [24], in the same way as the data from [25] served for validating the numerical model presented in [26], where a large-scale scenario with square longitudinal obstacles was considered. Another example of such an approach is given in [27], where the test data from [28] were used to validate the masonry wall response.…”
Section: Resultsmentioning
confidence: 99%
“…The data presented in the current paper may be used as the validation input for the numerical, analytical, or experimental studies. For instance, the data would be useful to validate the numerical model discussed in [24], in the same way as the data from [25] served for validating the numerical model presented in [26], where a large-scale scenario with square longitudinal obstacles was considered. Another example of such an approach is given in [27], where the test data from [28] were used to validate the masonry wall response.…”
Section: Resultsmentioning
confidence: 99%
“…Different contour images represent typical moments of blast wave propagation, and different pressure values are represented by different colours. At the blast onset, a rarefaction happens in the explosive charge volume, because of the rapid fluid expansion [40]. In the model without a rocket, the high-temperature and high-pressure explosive products produced by the explosive expand and spread rapidly around, and the blast wave spreads outward in the form of approximate spherical wave.…”
Section: Analysis For Propagation Lawof Blast Wavementioning
confidence: 99%
“…Ambrosini et al [26] and Luccioni et al [27] studied the propagation of blast waves in an urban environment to determine the mass of explosives used in a terrorist attack. Benselama et al [20] showed that this type of study can be used to draw P-I iso-damage diagrams. Regarding the numerical tool, AUTODYN was used in [25][26][27] and Air3D in [16,[23][24].…”
Section: Street Channellingmentioning
confidence: 99%
“…Rigas and Sklavounos [19] performed a comparison between a numerical model made with CFX-5.6 code and experimental tests. Benselama et al [20] performed a parametric study on this topic, and Silvestrini et al [21] proposed a simplified method for estimating the overpressures from blast waves.…”
Section: Introductionmentioning
confidence: 99%